2018
DOI: 10.1111/1477-9552.12299
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Credit Policy on Rice Production in Myanmar

Abstract: Rural finance has long been an important tool for poverty reduction and rural development by donors and governments, but the impacts have been controversial. Measuring impact is challenging due to identification problems caused by selection bias and governments' targeted interventions, while randomised trial data are scarce and limited to contexts where little to no rural finance exists. Using an author-collected dataset, we provide insights on a large-scale long-lasting subsidised rice credit programme in Mya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Nevertheless, by 2017, mean rice yields increased by 0.6 t/ha (SD = 1.1) and closely reached the 2017 national average of 3.8 t/ha (FAO Statistics Division, 2020). This development demonstrates that rice farmers in Myanmar have benefited from the economic and agricultural reforms in the 2010s (Aung et al, 2019; Belton et al, 2021). No significant differences were found between adopters and non-adopters.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, by 2017, mean rice yields increased by 0.6 t/ha (SD = 1.1) and closely reached the 2017 national average of 3.8 t/ha (FAO Statistics Division, 2020). This development demonstrates that rice farmers in Myanmar have benefited from the economic and agricultural reforms in the 2010s (Aung et al, 2019; Belton et al, 2021). No significant differences were found between adopters and non-adopters.…”
Section: Discussionmentioning
confidence: 94%
“…The positive rice productivity trend can partially be associated with better access to financial resources for improving rice cultivation (Tun et al, 2015). Aung, Nguyen, and Sparrow (2019) found that the national credit policy has been particularly beneficial for the delta region, where an additional 1 USD of seasonal credit per acre is associated with an increase of USD 2.1–2.5 in rice income per acre and of USD 58–61 in total annual income. In general, the annual income of farmers more than doubled between 2012 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Aung et al. (2019) provide insights into a large‐scale subsidized credit program in Myanmar (formerly Burma), one of the poorest and isolated countries in Asia. Once again, the identification strategy relies on a credit provision rule, in this case, based on rice landholding size.…”
Section: Rdds By Economic Field (In Alphabetical Order)mentioning
confidence: 99%
“…Finally, Aung et al (2019) provide insights into a large-scale subsidized credit program in Myanmar (formerly Burma), one of the poorest and isolated countries in Asia. Once again, the identification strategy relies on a credit provision rule, in this case based on rice landholding size.…”
Section: Microcredit Programsmentioning
confidence: 99%